ChemInform Abstract: Speciation Control During Suzuki‐Miyaura Cross‐Coupling of Haloaryl and Haloalkenyl MIDA Boronic Esters. Issue 43 (October 2015) - Fyfe, James W. B.; Valverde, Elena; Seath, Ciaran P.; Kennedy, Alan R.; Redmond, Joanna M.; Anderson, Niall A.; Watson, Allan J. B.
Abstract The chemoselectivity of the formal homologation of boronic acid derivatives is found to be temperature controlled giving access to either BMIDA adducts at room temperature or boronic acid pinacol ester (Bpin) products at elevated temperature.